Nerve entrapments of the lower leg, ankle and foot in sport - McCrory, P.; Bell, S.; Bradshaw, C. (Sports Medicine, 2002)
Exercise-related leg pain is a common and yet difficult management problem in sports medicine. There are many common causes of such symptoms including stress fractures and muscle compartment syndromes. There are also a number of less common but important conditions including popliteal artery entrapment and nerve entrapment syndromes. Even for an astute clinician, distinction between the different medical causes may be difficult given that many of their presenting features overlap. This review highlights the common clinical presentations and raises a regional approach to the diagnosis of the neurogenic symptoms. In part, this overlapping presentation of different pathological conditions may be due to a common aetiological basis of many of these conditions namely, fascial dysfunction. The same fascial restriction that predisposes to muscle compartment syndromes may also envelop the neurovascular structures within the leg resulting in either ischaemic or neurogenic symptoms. For many athletes with chronic exercise-related leg pain, combinations of such problems often coexist suggesting a more widespread fascial pathology. In our clinical experience, we often label such patients as 'fasciopaths'; however, the precise pathophysiological basis of this fascial problem remains to be elucidated. This review discusses the various nerve entrapment syndromes in the lower limb that may result in exercise-related leg pain in the sporting context. The anatomy, clinical presentation, investigation, medical management and surgical treatment are discussed at length for each of the syndromes. It is clear from clinical experience that the outcome of surgical management of such syndromes fares much better where a clear dermatomal pain distribution is present or where focal weakness and/or sensory symptoms appropriate for the nerve are present. In many situations, however, nonspecific leg pain or vague nonlocalising sensory symptoms are present and in such situations, alternative diagnoses must be considered and investigated appropriately. As mentioned above, many different pathologies may coexist in the lower limb and may be a source of confusion for the clinician or alternatively may be the reason for poor treatment outcomes.